Failure rate in university students: analysis of its variation in the transition from face-to-face education to virtual education - Leva Apaza, Antenor (2023)
The article presents an exploratory and descriptive study of the failure rate of students of the professional school of mechanical and electrical engineering of a public university in Peru. The purpose is to identify if the level of failure has experienced any positive or negative variation when moving from the context of face-to-face education to virtual education, due to the state of health emergency. This study makes it possible to demonstrate an initial reference state, relevant for decision-making at the level of university academic management, through strategies that will increase the approval rate of this professional school. The results obtained indicate that the level of failure of the students has experienced a positive variation when moving from the face-to-face context to the virtual one, due to the increase in the average rate of failure from 25% to 34%. The results are equivalent to 242 students failed during the context of face-to-face education, and 438 students failed during the context of virtual education. In addition, it is visualized that the specialty subjects, where there are the largest number of failed students, are linked to the area of electrical engineering. Being the subject of Electrical Machines I, the one with the highest failure rate, with a total average of 43% during the context of face-to-face education and 48% during virtual education.